2003
DOI: 10.1002/ejoc.200300204
|View full text |Cite
|
Sign up to set email alerts
|

Dicyanocarbene and Its Isomers: A Matrix Spectroscopic Study

Abstract: Irradiation of matrix‐isolated dicyanodiazomethane (4) with 254 nm‐light leads to the dicyanocarbene 5, which, upon further photoexcitation, undergoes successive isomerizations until a photoequilibrium between the five C3N2 isomers dicyanocarbene (T‐5), cyanoisocyanocarbene (T‐6), 3‐cyano‐2H‐azirenylidene (S‐7), 3‐isocyano‐2H‐azirenylidene (S‐8), and diisocyanocarbene (S‐9) is reached. The preferential formation of a specific member of this group can be achieved by changing the wavelength of the irradiating li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
5
21
0
Order By: Relevance
“…General: Equipment used for vaporization of silicon, cocondensation of silicon atoms with a substrate molecule, and subsequent irradiation of the reaction products has been described before (preceding paper in this journal [2] ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…General: Equipment used for vaporization of silicon, cocondensation of silicon atoms with a substrate molecule, and subsequent irradiation of the reaction products has been described before (preceding paper in this journal [2] ).…”
Section: Methodsmentioning
confidence: 99%
“…Thermally generated silicon atoms react with compounds containing isolated [1] or conjugated [2] double bonds in an argon matrix at 10 K with formation of π-adducts, which can subsequently be isomerized to the corresponding insertion products by irradiation. [1,2] It was tempting to test whether the same type of reaction also occurs with substrate molecules possessing an aromatic π-system, the simplest example being benzene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 There have been several previous studies of NCCCN. [17][18][19][20][21] A matrix isolation measurement indicated a linear triplet structure, 21 but the 193 or 254 nm radiation used in that study induced isomerization between several high-energy isomers, including cyclic structures. A massspectrometric study with 13 C labeled NCCCN − showed loss of carbon upon reionization, suggesting the carbon atoms are scrambled via these cyclic intermediates upon neutralization of the anion by high-energy collisions.…”
Section: Introductionmentioning
confidence: 93%
“…A second aspect was even more important: in continuing our studies on carbenes [5] we had recently investigated dicyanocarbene and its isomers. [6] For their generation a different procedure had to be used, namely the photolysis of dicyanodiazomethane 6. The first product is triplet dicyanocarbene T-7, which upon further photoexcitation undergoes successive isomerizations until a photoequilibrium between the five C 3 N 2 isomers T-7, triplet cyano(isocyano)carbene T-8, singlet 3-cyanoazacyclopropenylidene S-9, singlet di(isocyano)carbene S-10, and singlet 3-(isocyano)azacyclopropenylidene S-11 is reached.…”
Section: Introductionmentioning
confidence: 99%